Trend of caesarean section at two Government Medical College in Madhya Pradesh, India over one year of time period: a retrospective comparative study - Mathur, Poonam; Patel, Alka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: There is a massive public interest and debate on both the cause and appropriateness of increasingly employing a surgical procedure to short circuit or entirely bypass labour and delivery. The indications of caesarean sections vary among institutions as there is no standard classification system exists for indications of C-Section. Present study analysed pattern of caesarean section at two tertiary centre in Madhya Pradesh, India. Methods: A structured proforma was filled up for every case and results were recorded on excel sheet. All the cases included in study were further divided in group 1 (deliveries conducted in year 2014-2015 at Govt. Medical College Indore, M.P.), group 2 (deliveries conducted at Govt. Medical College Rewa at same time. Comparative analysis between study group1 and group 2 was done using Pearson Chi square test. Results: In group 1 there were 10525 deliveries out of which 3705 were delivered by caesarean section (35.2%), in group 2 there were 8674 deliveries out of which 1182 were delivered by caesarean section (13.6%). This difference in caesarean section at both medical college may be due to the more no. of referrals from the periphery to the medical college Indore and having more no of private institutions and district hospital which cater the normal delivery. Conclusions: There is a reliable and reproducible framework is required for audit and analysis of Caesarean section trends in specific obstetric subgroups to permit comparisons of practice between different institutions and over time in the same institution.